THE IMPROVEMENT OF THE MEDICAL SERVICES THROUGH IMPLEMENTATION OF A MULTIFUNCTIONAL PLATFORM PROMED - Cristian Marius TOMA; Dragos AROTARITEI; Vasilica TOMA; Roxana ANTOHI (Romanian Dental Association for Education, 2013)
The paper describes the implementation of a multifunctional platform - PROMED - for diagnosis and medical decision optimization to improve quality and efficiency of healthcare services. The information platform will be used to manage medical activities, electronic medical records and will enable collaboration among all stakeholders involved in health care: patients which will participate actively in information process about their health; healthcare providers can access information about their patients; public health authorities will have access to public information and will be enabled to provide prevention plan and early warning about epidemic diseases. The multifunctional platform will use modern information technologies for increasing quality and efficiency of healthcare in the new information society.